Diurnal preference and sports performance : a subjective and genetic view - Kunorozva, Lovemore (Department of Molecular and Cell Biology, 2015)
[T]he purpose of this study was to describe the distribution of morning- or evening-preferring individuals (measured using the Horne-Östberg morningness-eveningness personality questionnaire) and PER3 VNTR polymorphism (from genomic DNA products extracted from human buccal cell samples amplified and digested with NcoI) within male Caucasian, trained cyclists (CYC, n=138), Ironman triathletes (IM, n=301) and an active, but non-competitive control population of Caucasian males (CON, n=120). In addition, performance was assessed in trained cyclists strongly preferring mornings or evenings at various times of day.